2015
DOI: 10.1111/petr.12611
|View full text |Cite
|
Sign up to set email alerts
|

The value of 18F‐FDG PET in pediatric patients with post‐transplant lymphoproliferative disorder at initial diagnosis

Abstract: PTLD is a serious complication of both solid organ and BMT. This study assessed whether (18) F-FDG PET, when added to CT scan, had additional value in the initial evaluation of PTLD in pediatric patients and whether PET/CT at baseline can reliably guide biopsy. This retrospective study evaluated 34 consecutive pediatric patients (14 female), aged 3.5-17.0 yr (mean age: 9.9 yr, s.d.: 4.9 yr), who had undergone (18) F-FDG PET/CT from May 2007 to December 2014 at initial diagnosis of PTLD following heart (n = 13)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 37 publications
1
63
0
Order By: Relevance
“…[ 9 ] PET and CT scan have been shown to be complementary to each other at initial diagnosis. [ 10 ] The diagnosis was confirmed in all our patients by histopathology with immunostaining suggesting B-cell origin. In one of our patients, reduction in immunosuppression after excision biopsy alone had been therapeutic despite the monomorphic nature of the disease.…”
Section: Discussionsupporting
confidence: 58%
“…[ 9 ] PET and CT scan have been shown to be complementary to each other at initial diagnosis. [ 10 ] The diagnosis was confirmed in all our patients by histopathology with immunostaining suggesting B-cell origin. In one of our patients, reduction in immunosuppression after excision biopsy alone had been therapeutic despite the monomorphic nature of the disease.…”
Section: Discussionsupporting
confidence: 58%
“…Positron emission computed tomography (PET-CT) and computed tomography (CT) are important radiologic imaging tools for the diagnosis of EBV-PTLDs [1,[39][40][41][42]. In studies in patients with signs and symptoms of PTLDs, PET-CT has demonstrated high sensitivity (90%), specificity (89%), and positive (85%) and negative (93%) predictive values and good capacity for discriminating PTLDs from nonmalignant diseases (88%, 89%, 85%, and 93%, respectively) [40,43].…”
Section: Diagnosis Of Ebv-ptldsmentioning
confidence: 99%
“…However, falsepositive and false-negative results are possible owing to metabolism changes at sites of infection or inflammation and a lower uptake of 18F-fluorodeoxyglucose in PTLDs involving the central nervous system (CNS) or T cell-derived [4]. In a study reported by Vali et al [41], PET-CT identified more sites of lesions than conventional CT scan (168 versus 134), whereas CT revealed 22 PET-CTnegative lesions and a combination of both resulted in higher positivity (92.3%) in guiding biopsy. That study indicated that PET-CT and CT are complementary in the initial staging of PTLDs and guidance of biopsies.…”
Section: Diagnosis Of Ebv-ptldsmentioning
confidence: 99%
“…Results of larger adult studies, including more than 10 patients, are outlined in Supplementary Table S1, highlighting the role of PET/CT. We have identified three studies that also included pediatric patients . In Takehana et al.’s study, 30 patients were included from which 19 were under 18 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Staging PET either detected occult lesions not identified on other imaging modalities or suggested malignancy in equivocal lesions in a significant number of patients. A large cohort of 34 pediatric patients has been published by Vali et al., which also evaluated the role of PET at diagnosis and staging alone unlike our study that also looked at reassessment following chemotherapy and end of treatment. They show PET has a higher sensitivity, resulting in upstaging in seven (21%) cases, although CT seems to have a higher sensitivity for gastrointestinal disease.…”
Section: Discussionmentioning
confidence: 99%